1998
DOI: 10.1136/sti.74.5.349
|View full text |Cite
|
Sign up to set email alerts
|

Tissue specific HPV expression and downregulation of local immune responses in condylomas from HIV seropositive individuals.

Abstract: Objective: To study the eVect of tissue specific human papillomavirus (HPV) expression and its eVect on local immunity in condylomas from HIV positive individuals. Methods: Biopsy specimens of eight penile and eight perianal condylomas from HIV seropositive individuals were analysed. Expression of viral genes (HIV-tat and HPV E7 and L1) was determined by RT-PCR. The status of local immunity also was determined by RT-PCR by measuring CD4, CD8, CD16, CD1a, HLA-DR, and HLA-B7 mRNA levels in the tissues. DiVerenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
2
2

Year Published

2001
2001
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(28 citation statements)
references
References 49 publications
0
24
2
2
Order By: Relevance
“…Previous studies have demonstrated local immunity differences between the penile or anal areas (Arany et al, 1998). However, in our study, we did not find any significant difference in anal versus penile wart clearances.…”
Section: Discussioncontrasting
confidence: 74%
“…Previous studies have demonstrated local immunity differences between the penile or anal areas (Arany et al, 1998). However, in our study, we did not find any significant difference in anal versus penile wart clearances.…”
Section: Discussioncontrasting
confidence: 74%
“…In addition, HPV transcription patterns in HIV-positive subjects differed from those in HIV-negative subjects with condylomata acuminata; transcription of HPV early (E7) genes was predominant in samples obtained from HIV-positive patients, whereas transcription of late (L1) genes was more common in samples obtained from HIV-negative patients [28]. In perianal condyloma tissue samples obtained from HIV-positive patients for biopsy, a negative correlation was seen between E7 gene expression and CD1 (Langerhans cell) mRNA levels [29]. A potential correlate of these findings is that reductions in the HIV RNA level may be associated with reduced E7 gene expression, leading to normalization of CD1 mRNA levels with return of Langerhans cells to the site of HPV infection.…”
Section: Discussionmentioning
confidence: 63%
“…[147][148][149] HIV-associated immunodysfunction and decreased immune surveillance of HPV-induced dysplasia are likely contributors. However, patients with successful immune reconstitution often do not show improvement of their dysplasia.…”
Section: Anal Sccmentioning
confidence: 99%